ANALISIS FAKTOR TERHADAP LOYALITAS PENGUNJUNG RESTORAN KHUSUS KAWULA MUDA JALAN KALIURANG KM. 5,6 YOGYAKARTA - Siti Rokhmi Fuadati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
In the city, restaurant is one of significant infrastructure, both for business and tourism. The competition of restaurant business is increasing and more interesting. This competition motivates the owners of restaurants to perform its unique. They have to be consumer-oriented. Brand loyalty is a strategic value for the company. In order to achieve Brand Loyalty, the owners should consider several factors. This research identifies and analyzes the factors which influence consumer in selecting restaurant and brand loyalties. The restaurant segmentation’s is the youth, with the age between 20-35 years old, with middle up status.The results of the research shows that the consumer perception in food and beverage, facilities, locations, price and services, the unique of ambiences, comfortable, and advertising have significant roles in influencing consumer’s loyalty. From all these factor, the unique ambience in Dapur Resto Yogyakarta achieved the highest attention from the youth, especially in Jln. Kaliurang KM. 5,6. The consumer may have meal and beverage while having the unique ambience in a restaurant, completed with others supporting facilities.